The nematicidal potentiality of some algal extracts and their role in enhancement the tomato defense genes against root knot - nematodes - Rehab Y. Ghareeb; Ibrahim A. Adss; Shokry R. Bayoumi; Deiaa E. El-Habashy (Egyptian Journal of Biological Pest Control, 2019)
Abstract The nematicidal effect of three marine algal, Ulva fasciata Delile (UF) (green algae), Corallina mediterranea, Corallina officinalis (red algae), extracts on egg hatching and second-stage juveniles (J2) mortality of root-knot nematode (Meloidogyne incognita) in vitro compared to the nematicide activity of Oxamyl 24% SL (5 ml/l) was investigated. Results revealed that all treatments at the applied concentrations suppressed the egg hatching in 3 days. In details, the algal strain Ulva fasciata Delile extract showed the highest activity in decreasing the eggs hatchability after 3 days with 87%. Consequently, all treatments significantly increased the mortality of J2 larvae after 12, 24, and 48 h compared to the control treated with distilled water. Under greenhouse conditions, all treatments in inoculated soils cultivated with tomato plants had reduced numbers of galls, egg-masses/plant, and the number of J2/250 g than the non-inoculated soil. The algal extract and the Oxamyl 24% SL (5 ml/l) increased the length and fresh weight of plant shoots and roots than the untreated. However, there were no differences in shoots and roots fresh weights and their lengths in the plant treated with Oxamyl 24% SL (5 ml/l) or the extracts of U. fasciata and Corallina officinalis. These results were closely similar to control. Both of peroxidase and polyphenol enzymes activity for the control plants remained relatively stable, while the activity of the two enzymes in the plant inoculated with the nematode decreased during 2 to 18 day post inoculation (dpi). These activities increased in inoculated plants treated with C. officinalis, C. mediterranea, and U. fasciata extracts and the other plants treated with Oxamyl 24% SL (5 ml/l). The maximum activity of the three enzymes was recorded at 5 dpi after treatment with U. fasciata.